2019
DOI: 10.1155/2019/5608652
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Hybrid Fluoroquinolone-Boron Complexes and Their Evaluation in Cervical Cancer Cell Lines

Abstract: Quinolones are a family of antimicrobial agents that have been used in antibacterial and anticancer chemotherapy. Fluoroquinolone targets DNA gyrase and topoisomerase IV enzymes affecting several cellular processes, like cell death and proliferation; the best way to act is in the form of carboxylic acid or, recently, as quinolone-metal complex. In this work, the use of boron is shown as an alternative of metal to form a complex by incorporating to fluoroquinolone as an electron withdrawing substituent to activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Up to now, developmental benefits of the B have been shown in various studies [19,20]. B compounds have been used in prostate, lung, cervical, and breast cancer and caused positive effects against cancer [11,13,[21][22][23]. The supporting effect of B was demonstrated in patients who received chemotherapy [11].…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, developmental benefits of the B have been shown in various studies [19,20]. B compounds have been used in prostate, lung, cervical, and breast cancer and caused positive effects against cancer [11,13,[21][22][23]. The supporting effect of B was demonstrated in patients who received chemotherapy [11].…”
Section: Discussionmentioning
confidence: 99%
“…Boron complexes of some C7 modified fluoroquinolones achieved the antiproliferative activity on the human cervical carcinoma SiHa and CasKi cell lines. Hydantoin and dihydropyridine functionalized derivatives, compounds 59 and 60 , experienced the highest activity toward SiHa and CasKi cell lines, respectively at 0.75 mM after 72 hr of incubation . 1,10‐Phenanthroline and 2,2'‐bipyridyl copper(II) complexes with sparafloxacin were also potent antitumor agents.…”
Section: Fluoroquinolone Metal Ion Complexes With Anticancer Activitymentioning
confidence: 99%
“…Boron has been shown to strengthen the immune system, improve brain functions, modify hormone levels, and prevent osteoporosis, rheumatism, and vaginal infections in humans. Cancer treatments featuring boron, known as boron neutron capture therapy (BNCT), have been successful in treating cancerous cells with minimum damage to healthy cells tissues, [26–29] few examples of fluoroquinolone derivatives containing boron‐based substituents have been reported in the literature [30–33] …”
Section: Introductionmentioning
confidence: 99%
“…Cancer treatments featuring boron, known as boron neutron capture therapy (BNCT), have been successful in treating cancerous cells with minimum damage to healthy cells tissues, [26][27][28][29] few examples of fluoroquinolone derivatives containing boron-based substituents have been reported in the literature. [30][31][32][33] On the one hand, only a few fluoroquinolone-boron compounds exhibited antibacterial activity, [33] or antiproliferative activity in cancerous cell strains. [30] On the other hand, molecular docking calculations of derivatives of norfloxacinboron complexes with vascular endothelial growth factor receptor (VEGFRTK) showed that boron nuclei allowed a favorable interaction with the receptor; [34] this interaction was enhanced when the boron atom is bonded to fluorine atoms.…”
Section: Introductionmentioning
confidence: 99%